2016
DOI: 10.2174/2210289201607010001
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Oleuropein and Peracetic Acid as Sanitizing Agents for Inactivation of Biofilms

Abstract: The development of more efficient sanitizers for reducing the biofilm produced by pathogenic bacteria is of great importance, especially in the food industry. The aim of this study was to conduct a preliminary evaluation of the efficiency of oleuropein (OLE), extracted from olive leaves, and peracetic acid (PAA), alone or in combination, to inactivate biofilms formed by a strong biofilm-producer strain of Listeria monocytogenes (ATCC 7644). A disk diffusion method was also used to assess the susceptibility of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 28 publications
1
4
0
2
Order By: Relevance
“…However, data reported in this study and those previously mentioned works are not fully comparable because they used olive extracts that may contain other active phenolic compounds, instead of the isolated OLE. The lower BFI and reduction values for S. aureus treated with PAA + OLE, compared with PAA alone, corroborates the additive effect of PAA and OLE on planktonic cells of S. aureus using the disk diffusion method, and also agrees with a previous report describing increased inactivation of Listeria monocytogenes biofilms by OLE and PAA [10].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, data reported in this study and those previously mentioned works are not fully comparable because they used olive extracts that may contain other active phenolic compounds, instead of the isolated OLE. The lower BFI and reduction values for S. aureus treated with PAA + OLE, compared with PAA alone, corroborates the additive effect of PAA and OLE on planktonic cells of S. aureus using the disk diffusion method, and also agrees with a previous report describing increased inactivation of Listeria monocytogenes biofilms by OLE and PAA [10].…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies have indicated that oleuropein (OLE), a phenolic compound extracted from olive leaves, was effective against planktonic cells of several pathogens [8,9]. Dominciano et al [10] observed that OLE alone in solution at 4.0 mg mL -1 had no effect on Listeria monocytogenes biofilms, but the combination of OLE with PAA resulted in greater inactivation of L. monocytogenes cells in biofilms. The aim of this study was to conduct a preliminary evaluation of the antimicrobial activity of OLE and PAA, alone or in combination, on S. aureus and E. coli cells in suspension and in mono-species biofilms formed on surfaces of polystyrene microplates and stainless steel.…”
Section: Introductionmentioning
confidence: 99%
“…B. cereus is a rod-shaped, facultative aerobic and Gram-positive bacterium that can form spores, with significant impact on human health Enzyme-based control of biofilms in dairy industries formed biofilms, regular and effective cleaning methods are usually useful to prevent bacterial cells' initial adhesion on surfaces in the dairy industry. For this reason, food quality programmes, such as Good Manufacturing Practices, Sanitation Standard Operating Procedures, and Hazard Analysis and Critical Control Points, are fundamental tools to ensure effective cleaning and disinfection in food production environments (Cusato et al, 2014), thus avoiding the adhesion of bacterial cells and subsequent formation of biofilms on surfaces (Dominciano et al, 2016). In this context, the process of cleaning-inplace (CIP) is considered a central point in the biofilm control, provided that sanitisers are used to ensure the inactivation of microorganisms (Srey et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In this context, the process of cleaning-inplace (CIP) is considered a central point in the biofilm control, provided that sanitisers are used to ensure the inactivation of microorganisms (Srey et al, 2013). The correct application of biocides during the CIP process is crucial for reducing the bacterial load at the end of the disinfection procedure (Dominciano et al, 2016). However, pipe connections, valves and other places with difficult access for biocides are the main obstacles for proper cleaning of dairy processing lines, thus representing potential biofilm formation (Marchand et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation